Reinterpreting Gender Justice in Islamic Inheritance Law: A Critical Analysis of The Compilation of Islamic Law (Program Studi Hukum Keluarga Islam, 2025)
This article examines gender justice in Islamic inheritance law through a critical analysis of the Indonesian Compilation of Islamic Law (Kompilasi Hukum Islam/KHI) in response to contemporary socio-economic changes. The Qur’anic inheritance ratio of two-to-one between male and female heirs has long generated debate, particularly in relation to modern claims of gender equality. This study argues that Islamic inheritance law conceptualizes justice as proportional and responsibility based rather than strictly numerical equality, and therefore must be understood within its normative and social framework. Using a normative juridical method with a qualitative approach, this article analyzes primary legal sources, including the Qur’an, classical fiqh, and the KHI, alongside contemporary scholarship on gender justice and Maqāṣid al-Sharīʿah. The findings reveal that classical inheritance norms were historically grounded in the assumption of men as primary economic providers an assumption increasingly challenged by the growing economic participation of women in Indonesian Muslim society. The article further demonstrates that the KHI operates as a form of contextual ijtihād by accommodating gender responsive mechanisms such as consensual inheritance agreements and substitute heirs, without departing from Islamic legal principles. This study contributes to Islamic family law discourse by bridging normative doctrine and socio-legal realities, offering a contextual framework for realizing substantive gender justice while preserving the foundational objectives of Sharīʿa.